2014
DOI: 10.1007/s00248-014-0517-z
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of the Airborne Environment in Urban Spaces

Abstract: The organisms in aerosol microenvironments, especially densely populated urban areas, are relevant to maintenance of public health and detection of potential epidemic or biothreat agents. To examine aerosolized microorganisms in this environment, we performed sequencing on the material from an urban aerosol surveillance program. Whole metagenome sequencing was applied to DNA extracted from air filters obtained during periods from each of the four seasons. The composition of bacteria, plants, fungi, invertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 38 publications
(39 reference statements)
6
60
1
Order By: Relevance
“…Furthermore, the studies that have examined airborne eDNA have tended to focus solely on pollen and potentially have overlooked other eDNA sources and elements of the ecology of airborne eDNA. Typically, airborne eDNA research has mainly discussed findings in relation to human allergens and other aspects of human health (Be et al, ; Craine et al, ; Folloni et al, ; Korpelainen & Pietilainen, ; Kraaijeveld et al, ). Building upon these studies, Johnson, Cox, and Barnes () found that airborne eDNA could detect both wind‐pollinated Bouteloua genus and insect pollinated honey mesquite ( Prosopis glandulosa Torr.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the studies that have examined airborne eDNA have tended to focus solely on pollen and potentially have overlooked other eDNA sources and elements of the ecology of airborne eDNA. Typically, airborne eDNA research has mainly discussed findings in relation to human allergens and other aspects of human health (Be et al, ; Craine et al, ; Folloni et al, ; Korpelainen & Pietilainen, ; Kraaijeveld et al, ). Building upon these studies, Johnson, Cox, and Barnes () found that airborne eDNA could detect both wind‐pollinated Bouteloua genus and insect pollinated honey mesquite ( Prosopis glandulosa Torr.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, commonly used sampling equipment and typically culture‐dependent survey methods have been designed specifically to find pathogenic fungi (Weissfeld et al., ). More recently, cultivation‐independent survey methods and DNA identification techniques have been developed, giving the opportunity to record the presence of also many other fungal groups (Be et al., ; Hoisington, Maestre, King, Siegel, & Kinney, ; Peccia & Hernandez, ). Most widely used cultivation‐independent spore sampling techniques do not capture spores directly from the air but rely on the spore deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Most widely used cultivation‐independent spore sampling techniques do not capture spores directly from the air but rely on the spore deposition. Such sampling techniques include filter traps (Be et al., ; Castaño et al., ; Kivlin, Winston, Goulden, & Treseder, ), collecting surfaces such as Petri dishes (Adams, Miletto, Taylor, & Bruns, ) or filtering spores from rainwater (Peay & Bruns, ; Peay, Schubert, Nguyen, & Bruns, ). More recently developed “air samplers” (or “cyclone samplers”) sample spores directly from air and provide thus a more direct and efficient possibility to explore atmospheric biodiversity (West & Kimber, ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, metagenomics has been used to characterize viral communities in aerosols in only three studies (Whon et al, 2012;Hall et al, 2013;Be et al, 2015). In all of these studies, RNA viruses were excluded, despite the fact that most human respiratory viruses have RNA genomes such as coronavirus, influenza virus, and metapneumovirus.…”
Section: Introductionmentioning
confidence: 99%